THE MAIN FACTORS OF INFLUENCE OF EXTREME CONDITIONS OF SERVICE AND COMBAT ACTIVI - Kapliuchenko, O; Prykhodko, I. (Honor and Law, 2020)
The article considers the influence of extreme conditions of military service on the motivational component of moral and psychological state (MPS) of the National Guard of Ukraine staff. It is proved that extreme conditions of service and combat activity have both negative and positive influence on the motivation of personnel of the National Guard of Ukraine. The main category through which the psychological capabilities of the personnel of the armed formation are described is the moral and psychological state of the personnel. The analysis of scientific works shows the lack of common approaches to determine the set of factors that affect the motivational component of the psychological potential of the MPS of the personnel in the extreme conditions of service and combat activities. In general, it is proved that the extreme conditions of professional activity of specialists of risky professions are always associated with the negative impact of various factors on their MPS. The current state of motivation should be the object of constant monitoring and actual support in extreme conditions of service and combat activities. MPS of the personnel of the National Guard of Ukraine is an integral indicator of professional and psychological readiness of personnel to perform their duties during the implementation of service and combat activities in extreme conditions. The psychological component includes motivational, value-semantic and communicative components. The professional component includes military, professional (special) and physical components. Both the negative and positive factors influence the motivational component of the psychological potential of the MPS of the personnel of the National Guard of Ukraine during the performance of service and combat activities in extreme conditions. Factors of negative impact on the MPS, which are demotivators of service and combat activities, include vital, social and professional factors. The factors of positive influence on the MSP of the personnel of the National Guard of Ukraine, which are the motivators of service and combat activities and improve the quality of service and combat activities implementation, also include vital, social and professional factors.